Estimation fish stock and composition using mark recapture studies in floodplain lake, Jambi City - Siswanta Kaban; Samuel Samuel; Makri Makri (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Fish stock assessment can be estimated by dependent and independent sampling; Mark-recapture studies is a part of independent sampling method that can be used for it. This study was conducted in 2018 using purposive sampling methods. The purpose of this study was to determine the current status of fish stocks and the composition of fish species in the floodplain/oxbow lake, Jambi city. Interviews were conducted to determine the types of fish in this area as a reference, and then, the composition of fish species, modification of fishing gear and combine with mark-recapture sampling. The total catch was 66.5 Kg, with the dominant compositions were Hemibagrus nemurus (42%), Pangasius sp (20%), Channa lucius (12%) and the others were 26% (Osteochilus haseselti, Osteochilus bornensis, Barbonymus schwanenfeldi, Labiobarbus festivus, Thynnichthys polylepis, Mystus sp, Cryptopterus spp, Bothia macrocanthus, Labeo chrysophekadion, Barbycthys loevis and Macrobrachium rosenbergii). The conversion result of fish catches with the total area, which has been assessed using Mark-recapture studies, was 558.6 kg/ha. Finally, the total area of the floodplain was estimated at 60137 ha, and the fish stock was 66.4151.7 tons. Its showed that, allowable catch should be under this value, and Mark-recapture studies is one simple methods can be used to predict fish stock in floodplain areas.Keywords:Fish stockfloodplain lakeMark recapturemanagement